1835: The sixth legislature and the transition to centralism in Michoacán (Tzintzun, Revista de Estudios Históricos, 2021)
The present article analyzes the debates of Michoacánâ€™s Sixth Congress on the transition of the government system toward centralism demanded from severalmunicipalities and towns in the state. The consulted documents show that arguments on the matter took place amidst the division of the legislature itselfand under the pressure coming from several town halls and the armed forces that were seeking the AssemblyÂ´s pronouncement on favor of adopting centralism.
Keywords: federalism; Legislative Power; systemâ€™s reforms; Armed Forces; First Centralist Republic